Comparing nectarivorous butterfly species under different agricultural landscape - Abdul Aziz, Nurul Amalina (2018)
Conversion of forest areas for agricultural purposes has contributed to the decline of overall biodiversity. Among the major organism being affected, insects provide substantial evidence on the impact of conversion of forest areas. The present study was set out to investigate the abundance and species richness of butterflies (Insecta:Lepidoptera) in three different agricultural landscapes namely; orchard (polyculture systems), oil palm and rubber plantations (monoculture systems) in Kampung Sungai Lalah, Pedas, Negeri Sembilan. In this study, butterflies were sampled using active sampling methods (visual observations) in all study sites (a total of 45 sampling points). Throughout the study, orchard (polyculture systems) represent a significantly greater butterfly abundance (276) and species richness (14) followed by oil palm and rubber plantations. The findings suggest that polyculture systems in orchard can provide refuge for diverse butterfly community due to greater habitat heterogeneity compared to oil palm and rubber plantations. In addition, vegetation cover and height showed a positive relationship on butterfly abundance and richness showing their importance at all agricultural landscapes. The present study suggest that polyculture systems in agricultural landscapes is essential to improve insects biodiversity especially butterflies. Hence, more studies are required to assess the impacts of polyculture and monoculture practices in different agricultural areas in Malaysia.